Surface-treated copper foil, method for producing the same, and negative electrode for secondary battery including the surface-treated copper foil

By treating the copper foil surface, the problem of high interface resistance and insufficient adhesion between the negative electrode current collector and the active material in the secondary battery is solved, low interface resistance and high adhesion strength are achieved, and the charging/discharging efficiency of the battery is improved.

CN114788054BActive Publication Date: 2025-04-15LOTTE ENERGY MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN201980102949.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-19
Filing Date
2019-12-20
Publication Date
2025-04-15
Estimated Expiration
2039-12-20

AI Technical Summary

Technical Problem

The interface resistance between the negative electrode current collector and the active material in the secondary battery is high, resulting in a decrease in charging/discharge efficiency, and insufficient adhesion between the active material and the current collector, resulting in a concentration of current and increasing the internal resistance of the negative electrode.

Method used

By surface treatment of the copper foil, needle-shaped copper particles are formed, with an average long axis length of about 0.6 μm to 2.0 μm and a distance between each other is about 1 μm to 5 μm, forming copper foils with low interface resistance and high bond strength.

Benefits of technology

Low interface resistance and high bonding strength with the negative electrode active material are achieved, the charging/discharging efficiency of the secondary battery is improved, and the internal resistance of the negative electrode is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114788054B_ABST
    Figure CN114788054B_ABST
Patent Text Reader

Abstract

The present invention discloses a surface-treated copper foil for a negative electrode collector of a secondary battery; a method for manufacturing the surface-treated copper foil; and a negative electrode for a secondary battery comprising the surface-treated copper foil, wherein needle-shaped copper particles having an average major axis length of about 0.6 μm to about 2.0 μm on at least one surface of the copper foil are spaced apart by a distance of about 1 μm to about 5 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface-treated copper foil, a method for manufacturing the surface-treated copper foil, and a negative electrode for a secondary battery comprising the surface-treated copper foil. More specifically, the present invention relates to a surface-treated copper foil having low interface resistance with a negative electrode active material and good bonding strength to the negative electrode active material, a method for manufacturing the surface-treated copper foil, and a negative electrode for a secondary battery comprising the surface-treated copper foil. Background Art

[0002] A secondary battery is an energy conversion device that stores electrical energy in the form of chemical energy and then generates electricity by reconverting the stored energy into electrical energy as needed. Among these secondary batteries, lithium secondary batteries are currently widely used due to their high operating voltage, high energy density, and good life characteristics.

[0003] A lithium secondary battery is composed of a positive electrode, a negative electrode, a separator and an electrolyte. The positive electrode is formed by a positive electrode current collector coated with a positive electrode active material layer, and the negative electrode is formed by a negative electrode current collector coated with a negative electrode active material layer. As a negative electrode current collector, electrolytic copper foil is generally used. Since the negative electrode includes two different materials in contact with each other, that is, a current collector and an active material, an interface resistance will occur at the negative electrode. High interface resistance leads to a decrease in charge / discharge capacity and, therefore, a decrease in battery efficiency.

[0004] Due to the deterioration or expansion of the secondary battery, or external impact, the active material may be partially peeled off from the collector. Specifically, the deterioration or expansion of the secondary battery, or physical forces such as external impact weaken the adhesion of the active material to the surface of the collector, resulting in the formation of a gap between the collector and the active material. As a result, the surface area along which the current and electrons will move is reduced, resulting in the current and electrons being concentrated at a specific point, which leads to an increase in the internal resistance of the negative electrode. Summary of the invention

[0005] [Technical issues]

[0006] One aspect of the present invention is to provide a surface-treated copper foil having low interface resistance with a negative electrode active material, a method for manufacturing the surface-treated copper foil, and a negative electrode for a secondary battery including the surface-treated copper foil.

[0007] Another aspect of the present invention is to provide a surface-treated copper foil having good bonding strength to a negative electrode active material, a method for manufacturing the surface-treated copper foil, and a negative electrode for a secondary battery including the surface-treated copper foil.

[0008] [Technical solution]

[0009] 1. According to one aspect of the present invention, a surface-treated copper foil for a negative electrode collector for a secondary battery is provided. The surface-treated copper foil includes needle-shaped copper particles formed on at least one surface thereof, wherein the average major axis length of the copper particles is about 0.6 μm to about 2.0 μm, and the distance between each other is about 1 μm to about 5 μm.

[0010] 2. In Embodiment 1, the aspect ratio of the copper particles may be about 1.5 to about 10.

[0011] 3. In embodiment 1 or 2, the surface-treated copper foil may have a thickness of about 1 μm to about 100 μm.

[0012] 4. In any one of embodiments 1 to 3, the interface resistance of the surface-treated copper foil may be lower by about 10% or more than that of the untreated copper foil.

[0013] 5. In any one of embodiments 1 to 4, the interface resistance of the surface-treated copper foil may be about 0.0025 ohm / m 2 To about 0.0032ohm / m 2 .

[0014] 6. In any one of embodiments 1 to 5, the bonding strength of the surface-treated copper foil may be about 20% or more higher than that of the untreated copper foil.

[0015] 7. In any one of Embodiments 1 to 6, the surface-treated copper foil may have an adhesive strength of about 3 gf / mm to about 5 gf / mm.

[0016] 8. In any one of embodiments 1 to 7, the surface-treated copper foil may further include an anti-rust layer covering the copper particles, wherein the anti-rust layer may include an inorganic anti-rust layer, an organic anti-rust layer, or a combination thereof.

[0017] 9. In embodiment 8, the inorganic antirust layer may include chromium (Cr), nickel (Ni), cobalt (Co), or alloys or combinations thereof, and the organic antirust layer may include azole compounds, silane compounds, or combinations thereof.

[0018] 10. According to another aspect of the present invention, there is provided a method for manufacturing a surface-treated copper foil according to any one of embodiments 1 to 9. The method comprises: immersing the copper foil in a primary electrolyte containing about 5 g / L to about 15 g / L of a nickel salt and about 5 g / L to about 20 g / L of a copper salt, and then heating the copper foil at a liquid temperature of about 25° C. to about 45° C. and at a temperature of about 1 A / dm 2 To about 5A / dm 2The copper foil is electrolyzed at a current density of about 1 second to 5 seconds to perform a primary plating; and the copper foil is immersed in a secondary electrolyte containing about 40 g / L to about 70 g / L of a copper salt and about 100 g / L to about 150 g / L of sulfuric acid, and then at a liquid temperature of about 25° C. to about 45° C. and about 10 A / dm 2 To about 20A / dm 2 The secondary plating is performed by electrolyzing for about 1 second to 5 seconds at a current density of 1.50 nm.

[0019] 11. According to another aspect of the present invention, a negative electrode for a secondary battery is provided, the negative electrode comprising: a surface-treated copper foil according to any one of embodiments 1 to 9, or a surface-treated copper foil manufactured by the method according to embodiment 10; and a negative electrode active material coated on the surface-treated copper foil.

[0020] 12. In embodiment 11, the negative electrode active material may include carbon, metal, metal oxide, metal carbide or a combination thereof.

[0021] [Beneficial Effects]

[0022] The present invention provides a surface-treated copper foil having low interface resistance with a negative electrode active material and good bonding strength to the negative electrode active material, a method for manufacturing the surface-treated copper foil, and a negative electrode for a secondary battery comprising the surface-treated copper foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) to Figure 1 (d) are SEM photographs of the surface-treated copper foils produced in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively. DETAILED DESCRIPTION

[0024] As used herein, the singular forms “a”, “an” and “the” are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0025] Throughout the specification, similar components will be denoted by similar reference numerals. In addition, descriptions of known functions and configurations that may unnecessarily obscure the subject matter of the present invention will be omitted.

[0026] It will be understood that when an element is referred to as being “on,” “over,” “under,” or “beside” another element, unless such term is preceded by “directly” there may be one or more intervening elements between the two elements.

[0027] It should also be understood that when the terms "includes," "comprising," "containing," and / or "having" are used in this specification, they refer to the presence of the stated features, integers, steps, operations, elements, components, and / or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or combinations thereof.

[0028] As used herein, when explaining a component, a numerical value related to a certain component is interpreted as including a tolerance range unless expressly stated otherwise.

[0029] As used herein, the expression “a to b” indicating a specific numerical range means “greater than or equal to a and less than or equal to b (a≤ and ≤b)”.

[0030] As used herein, the term "aspect ratio" may refer to the ratio of the longest diameter of a copper particle to the shortest diameter of the copper particle in a cross-sectional view (major axis length / minor axis length or length / width). The longest diameter of a copper particle is referred to as the "major axis length", and the shortest diameter of a copper particle is referred to as the "minor axis length".

[0031] As used herein, "distance between copper particles" refers to the shortest distance between copper particles.

[0032] As used herein, “interface resistance” refers to a value obtained by the following method, in which 6 g of artificial graphite is mixed with 6.3 g of carboxymethyl cellulose (CMC) (2% aqueous solution), 0.32 g of styrene-butadiene rubber (SBR) and 1 ml of distilled water to prepare a negative electrode active material slurry, the negative electrode active material slurry is coated on a surface-treated copper foil (15 cm×15 cm) with a scraper at a thickness of 60 μm to 80 μm, and then dried at 130° C. for 1 hour, and then the interface resistance of the prepared sample is measured using an interface resistance measuring device under the following conditions: current: 10 mA, speed: normal, voltage range: 0.5 V.

[0033] As used herein, “adhesion strength” refers to a value obtained by a method in which a negative electrode active material is coated on a surface-treated copper foil in the same manner as when measuring the interface resistance, and dried, and then a double-sided tape is attached to the surface of the surface-treated copper foil coated with the negative electrode active material, followed by measuring the peel strength of the prepared sample at a peel angle of 90° using a tensile tester.

[0034] After conducting intensive research on a copper foil for a negative electrode current collector capable of improving the charge / discharge efficiency of a secondary battery, the inventors of the present invention have completed the present invention based on the following confirmation, that is, when a negative electrode current collector for a secondary battery is formed of a surface-treated copper foil including acicular copper particles on at least one surface thereof, wherein the average major axis length of the copper particles is from about 0.6 μm to about 2.0 μm (e.g., about 0.6 μm, about 0.7 μm, about 0.8 μm, about 0.9 μm, about 10 μm, about 25 μm, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 70 μm, about 80 μm, about 90 μm, about 100 μm, about 150 μm, about 160 μm, about 170 μm, about 180 μm, about 190 μm, about 200 μm, about 210 μm, about 220 μm, about 230 μm, about 240 μm, about 250 μm, about 260 μm, about 270 μm, about 280 μm, about 290 μm, about 300 μm, about 310 μm, about 320 μm, about 330 μm, about 340 μm The plurality of layers of the plurality of layers of the plurality of layers of the plurality of layers of the plurality of layers of the plurality of layers of the plurality of layers of the plurality of layers are preferably about 0.9 μm, about 1.0 μm, about 1.1 μm, about 1.2 μm, about 1.3 μm, about 1.4 μm, about 1.5 μm, about 1.6 μm, about 1.7 μm, about 1.8 μm, about 1.9 μm, or about 2.0 μm), and are spaced from each other by a distance of about 1 μm to about 5 μm (e.g., about 1.1 μm, about 1.2 μm, about 1.3 μm, about 1.4 μm, about 1.5 μm, about 1.6 μm, about 1.7 μm, about 1.8 μm, about 1.9 μm, or about 2.0 μm). , about 1.7μm, about 1.8μm, about 1.9μm, about 2μm, about 2.1μm, about 2.2μm, about 2.3μm, about 2.4μm, about 2.5μm, about 2.6μm, about 2.7μm, about 2.8μm, about 2.9μm, about 3μm, about 3.1μm, about 3.2μm, about 3.3μm, about 3.4μm, about 3.5μm, about 3.6μm, about 3.7μm, about 3.8μ When the acicular copper particles are 2.5 μm, 3.9 μm, 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm or 5 μm, the acicular copper particles can better wrap the negative electrode active material than the spherical or polygonal copper particles, so that low interface resistance with the negative electrode active material and high bonding strength to the negative electrode active material can be achieved. In one embodiment, the average major axis length of the acicular copper particles may be from about 0.7 μm to about 1.6 μm (e.g., from about 0.7 μm to about 1.5 μm), and the distance between each other may be from about 1 μm to about 4.5 μm (e.g., from about 1.2 μm to about 4.1 μm), but is not limited thereto.

[0035] Although the method for forming the acicular copper particles on the surface of the copper foil is not particularly limited, the acicular copper particles can be formed, for example, by electroplating the copper foil twice. The primary electrolyte can be a nickel salt containing about 5 g / L to about 15 g / L (for example, about 5 g / L, about 6 g / L, about 7 g / L, about 8 g / L, about 9 g / L, about 10 g / L, about 11 g / L, about 12 g / L, about 13 g / L, about 14 g / L, or about 15 g / L, as another example, about 8 g / L to about 14 g / L) and about 5 g / L to about 20 g / L (for example, about 5 g / L, about 6 g / L, about 7 g / L, about 8 g / L, about 9 g / L, about 10 g / L, about 11 g / L, about 12 g / L, about 13 g / L, about 14 g / L, or about 15 g / L, as another example, about 8 g / L to about 14 g / L). In some embodiments, the present invention relates to an aqueous solution of a copper salt containing about 1 g / L, about 9 g / L, about 10 g / L, about 11 g / L, about 12 g / L, about 13 g / L, about 14 g / L, about 15 g / L, about 16 g / L, about 17 g / L, about 18 g / L, about 19 g / L, or about 20 g / L, and as another example, about 10 g / L to about 17 g / L) and the pH adjusted to about 1 to about 5 (e.g., about 1, about 2, about 3, about 4, or about 5, and as another example, about 2 to about 4). Within these ranges, seeds of needle-shaped copper particles can be smoothly formed. The secondary electrolyte may be an aqueous solution containing about 40 g / L to about 70 g / L (e.g., about 40 g / L, about 45 g / L, about 50 g / L, about 55 g / L, about 60 g / L, about 65 g / L, or about 70 g / L, and as another example, about 45 g / L to about 60 g / L) of a copper salt and about 100 g / L to about 150 g / L (e.g., about 100 g / L, about 105 g / L, about 110 g / L, about 115 g / L, about 120 g / L, about 125 g / L, about 130 g / L, about 135 g / L, about 140 g / L, about 145 g / L, or about 150 g / L, and as another example, about 120 g / L to about 140 g / L) of sulfuric acid. Within these ranges, needle-shaped copper particles can be well formed on the seed crystals. Examples of nickel salts may include nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate, but are not limited thereto. The above nickel salts may be used alone or as a mixture thereof. Examples of copper salts may include copper sulfate, copper nitrate, copper chloride, and copper acetate, but are not limited thereto. The above copper salts may be used alone or as a mixture thereof. For example, an insoluble electrode as a positive electrode and an untreated copper foil as a negative electrode may be immersed in a primary electrolyte, followed by a liquid temperature of about 25°C to about 45°C (e.g., about 25°C, about 30°C, about 35°C, about 40°C, or about 45°C) and about 1A / dm 2 To about 5A / dm 2 (For example, about 1A / dm 2 , about 2A / dm 2 , about 3A / dm 2 , about 4A / dm 2 or about 5A / dm 2) for about 1 second to 5 seconds (e.g., about 1 second, about 2 seconds, about 3 seconds, about 4 seconds, or about 5 seconds) to perform primary electroplating, but is not limited thereto. For example, an insoluble electrode as a positive electrode and a copper foil that has been electroplated once as a negative electrode may be immersed in a secondary electrolyte, followed by heating at a liquid temperature of about 25° C. to about 45° C. (e.g., about 25° C., about 30° C., about 35° C., about 40° C., or about 45° C.) and about 10 A / dm 2 To about 20A / dm 2 (For example, about 10A / dm 2 , about 11A / dm 2 , about 12A / dm 2 , about 13A / dm 2 , about 14A / dm 2 , about 15A / dm 2 , about 16A / dm 2 , about 17A / dm 2 , about 18A / dm 2 , about 19A / dm 2 or about 20A / dm 2 ) for about 1 second to 5 seconds (e.g., about 1 second, about 2 seconds, about 3 seconds, about 4 seconds or about 5 seconds) to perform secondary electroplating, but is not limited thereto.

[0036] In one embodiment, the aspect ratio of the needle-shaped copper particles may be about 1.5 to about 10 (e.g., about 1.5, about 2, about 2.5, about 3, about 3.5, about 4, about 4.5, about 5, about 5.5, about 6, about 6.5, about 7, about 7.5, about 8, about 8.5, about 9, about 9.5, or about 10). Within this range, the needle-shaped copper particles may have a low interfacial resistance with the negative electrode active material and good bonding strength to the negative electrode active material. For example, the aspect ratio of the needle-shaped copper particles may be about 1.5 to about 7, or about 2 to about 5, but is not limited thereto.

[0037] In one embodiment, the minor axis length of the needle-shaped copper particles may be about 0.2 μm to about 0.6 μm (e.g., about 0.2 μm, about 0.3 μm, about 0.4 μm, about 0.5 μm, or about 0.6 μm). Within this range, the needle-shaped copper particles may have low interface resistance with the negative electrode active material and good bonding strength to the negative electrode active material. For example, the minor axis length of the needle-shaped copper particles may be about 0.3 μm to about 0.5 μm, but is not limited thereto.

[0038] In one embodiment, the surface-treated copper foil may have a thickness of about 1 μm to about 100 μm. Within this range, the surface-treated copper foil may be suitable for use as a negative electrode current collector. For example, the surface-treated copper foil may have a thickness of about 3 μm to about 80 μm or about 5 μm to about 60 μm, but is not limited thereto.

[0039] In one embodiment, the interfacial resistance of the surface-treated copper foil may be lower than that of the untreated copper foil by more than about 10%. For example, the interfacial resistance of the surface-treated copper foil may be lower than that of the untreated copper foil by about 10% to about 100% (e.g., about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or about 100%) or about 10% to about 30%, but is not limited thereto.

[0040] In one embodiment, the interface resistance of the surface treated copper foil may be 0.0025 ohm / m 2 To 0.0032ohm / m 2 (For example, about 0.0025 ohm / m 2 , about 0.0026ohm / m 2 , about 0.0027ohm / m 2 , about 0.0028ohm / m 2 , about 0.0029ohm / m 2 、About 0.0030ohm / m 2 , about 0.0031ohm / m 2 or about 0.0032ohm / m 2 ). For example, the interface resistance of the surface treated copper foil may be about 0.0025 ohm / m 2 To about 0.0031ohm / m 2 , or about 0.0027ohm / m 2 To about 0.0031ohm / m 2 , but not limited to this.

[0041] In one embodiment, the bonding strength of the surface-treated copper foil may be about 20% or more higher than that of the untreated copper foil. For example, the bonding strength of the surface-treated copper foil may be about 20% to about 100% (e.g., about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, or about 100%) or about 20% to about 50% higher than that of the untreated copper foil, but is not limited thereto.

[0042] In one embodiment, the surface treated copper foil may have an adhesive strength of about 3 gf / mm to about 5 gf / mm (e.g., about 3 gf / mm, about 3.1 gf / mm, about 3.2 gf / mm, about 3.3 gf / mm, about 3.4 gf / mm, about 3.5 gf / mm, about 3.6 gf / mm, about 3.7 gf / mm, about 3.8 gf / mm, about 3.9 gf / mm, about 4 gf / mm, about 4.1 gf / mm, about 4.2 gf / mm, about 4.3 gf / mm, about 4.4 gf / mm, about 4.5 gf / mm, about 4.6 gf / mm, about 4.7 gf / mm, about 4.8 gf / mm, about 4.9 gf / mm, or about 5 gf / mm). For example, the adhesive strength of the surface-treated copper foil may be about 3 gf / mm to about 4.5 gf / mm, or about 3 gf / mm to about 4 gf / mm, but is not limited thereto.

[0043] In one embodiment, the surface treated copper foil may further include an antirust layer covering the needle-shaped copper particles. The antirust layer may include an inorganic antirust layer, an organic antirust layer, or a combination thereof. The number of antirust layers is not particularly limited. The inorganic antirust layer may include, for example, chromium (Cr), nickel (Ni), cobalt (Co), or an alloy or combination thereof. The organic antirust layer may include an azole compound (for example, a benzotriazole compound), a silane compound, or a combination thereof. In one embodiment, the antirust layer may include a chromate antirust layer, which may be formed by, for example, treating with a liquid containing chromic anhydride, chromic acid, dichromic acid, chromate, dichromate, or a combination thereof, but is not limited thereto.

[0044] The surface-treated copper foil can be used as a negative electrode current collector for a secondary battery. The surface-treated copper foil used as a negative electrode current collector can exhibit low interface resistance with a negative electrode active material and good bonding strength to the negative electrode active material.

[0045] According to another aspect of the present invention, a negative electrode for a secondary battery is provided, which can be manufactured by coating the surface-treated copper foil with a negative electrode active material.

[0046] The negative electrode active material may include any known negative electrode active material without limitation. For example, the negative electrode active material may include carbon (e.g., artificial graphite, natural graphite, etc.), metal powder (e.g., lithium powder, tin powder, silicon powder, etc.), metal oxide (e.g., tin oxide, silicon oxide, etc.), metal carbide (e.g., silicon carbide, etc.), or a combination thereof.

[0047] According to still another aspect of the present invention, there is provided a secondary battery including the negative electrode for a secondary battery.

[0048] Next, the present invention will be described in more detail with reference to some examples. It should be understood that these examples are only for illustration and are not to be construed as limiting the present invention in any way.

[0049] Example

[0050] Example 1

[0051] The 8 μm thick copper foil (Nissin Materials Co., Ltd.) was immersed in a primary electrolyte containing 10 g / L nickel sulfate and 10 g / L copper sulfate, and then heated at a liquid temperature of 30°C, a pH of 2.5, and a flow rate of 2 A / dm 2 The copper foil was electrolyzed for 3 seconds at a current density of 14A / dm. The copper foil was then immersed in a secondary electrolyte containing 65 g / L of copper sulfate and 120 g / L of sulfuric acid, and then heated at a liquid temperature of 30°C and 14A / dm. 2 The copper foil was electrolyzed at a current density of 1000 nm for 3 seconds, thereby performing secondary plating on the obtained copper foil. Thereafter, a rust-proof layer was formed by the following method to manufacture a surface-treated copper foil: in this method, the obtained copper foil was immersed in an aqueous solution containing 2 g / L of chromic acid at 30° C. for 3 seconds, and then washed with water.

[0052] Example 2

[0053] A surface-treated copper foil was produced in the same manner as in Example 1, except that the amount of nickel sulfate used in the primary plating was changed to 11 g / L.

[0054] Example 3

[0055] A surface-treated copper foil was produced in the same manner as in Example 1, except that the amount of nickel sulfate used in the primary plating was changed to 12 g / L.

[0056] Example 4

[0057] A surface-treated copper foil was produced in the same manner as in Example 1, except that the amount of nickel sulfate used in the primary plating was changed to 13 g / L.

[0058] Comparative Example 1

[0059] A surface-treated copper foil was produced in the same manner as in Example 1, except that the primary electroplating and the secondary electroplating were omitted.

[0060] Comparative Example 2

[0061] A surface-treated copper foil was produced in the same manner as in Example 1, except that the amount of copper sulfate used in the primary plating was changed to 30 g / L.

[0062] Comparative Example 3

[0063] A surface-treated copper foil was produced in the same manner as in Example 1, except that nickel sulfate was not used in the primary plating.

[0064] The following properties of each of the surface-treated copper foils produced in Examples and Comparative Examples were evaluated.

[0065] Property evaluation

[0066] (1) Average major axis length of copper particles (unit: μm) and average distance between copper particles (unit: μm): A surface image of each surface-treated copper foil produced in Examples and Comparative Examples was obtained at a magnification of 5,000× using a scanning electron microscope, and then the major axis lengths of 50 copper particles and the distances between copper particles within an area of ​​100 μm×100 μm were measured, and then the measured values ​​were averaged.

[0067] (2) Interface resistance (unit: ohm / m 2 ): 6 g of artificial graphite (MAG-D, Hitachi Chemical Co., Ltd.) was mixed with 6.3 g of carboxymethyl cellulose (CMC) (2% aqueous solution), 0.32 g of styrene-butadiene rubber (SBR) and 1 ml of distilled water to prepare a negative electrode active material slurry, and the negative electrode active material slurry was coated on each surface-treated copper foil (15 cm×15 cm) manufactured in the embodiments and comparative examples with a thickness of 60 μm to 80 μm using a scraper (Micrometer Adjustable Film Applicator, Welcos Co., Ltd.), and then dried at 130° C. for 1 hour, and then the interface resistance of the prepared sample was measured using an interface resistance measuring device (XF057, Hioki Electric Co., Ltd.) under the following conditions: current: 10 mA, speed: normal, voltage range: 0.5 V.

[0068] (3) Adhesion strength (unit: gf / mm): In the same manner as when measuring the interface resistance, the negative electrode active material was applied to each of the surface-treated copper foils prepared in the Examples and Comparative Examples and dried. A double-sided tape was then attached to the surface of the surface-treated copper foil coated with the negative electrode active material to prepare a tensile specimen having a size of 30 mm×70 mm (width×length), and then the peel strength of the specimen was measured using a tensile tester at a peel angle of 90° and a peel rate of 50.8 mm / min.

[0069] Table 1

[0070]

[0071] From the results shown in Table 1, it can be seen that the surface-treated copper foils of Examples 1 to 4, whose shapes of copper particles, average major axis lengths of copper particles, and average distances of copper particles meet the conditions of the present invention, exhibit lower interface resistance and higher bonding strength than the surface-treated copper foils of Comparative Examples 1 to 3. Therefore, it can be seen that the surface-treated copper foils according to the present invention are particularly suitable for use as negative electrode collectors for secondary batteries.

[0072] Although some embodiments have been described herein, it should be understood that the present invention is not limited to the following embodiments and can be implemented in different ways, and those skilled in the art can make various modifications, changes, alterations, and implement equivalent embodiments without departing from the spirit and scope of the present invention. Therefore, it should be understood that these embodiments are provided only for illustration and are not interpreted as limiting the present invention in any way.

Claims

1. A surface-treated copper foil for a negative electrode collector for a secondary battery, the surface-treated copper foil comprising needle-shaped copper particles formed on at least one surface thereof, in, The copper particles have an average major axis length of 0.6 μm to 2.0 μm and are spaced apart from each other by a distance of 1 μm to 5 μm; and an aspect ratio of the copper particles is 1.5 to 10. 2 . The surface-treated copper foil according to claim 1 , wherein the surface-treated copper foil has a thickness of 1 μm to 100 μm.

3. The surface-treated copper foil according to claim 1 or 2, wherein the interface resistance of the surface-treated copper foil is lower than that of the untreated copper foil by more than 10%.

4. The surface-treated copper foil according to claim 1 or 2, wherein the interface resistance of the surface-treated copper foil is 0.0025 ohm / m 2 To 0.0032ohm / m 2 .

5. The surface-treated copper foil according to claim 1 or 2, wherein the bonding strength of the surface-treated copper foil is 20% or more higher than that of an untreated copper foil. 6 . The surface-treated copper foil according to claim 1 , wherein the surface-treated copper foil has an adhesive strength of 3 to 5 gf / mm.

7. The surface-treated copper foil according to claim 1 or 2, further comprising: The anti-rust layer covers the copper particles, and the anti-rust layer includes an inorganic anti-rust layer, an organic anti-rust layer or a combination thereof.

8. The surface-treated copper foil according to claim 7, wherein the inorganic anti-rust layer comprises chromium (Cr), nickel (Ni), cobalt (Co), or an alloy or a combination thereof, and the organic anti-rust layer comprises an azole compound, a silane compound, or a combination thereof.

9. A method for producing a surface-treated copper foil according to any one of claims 1 to 8, the method comprising: The copper foil is immersed in a primary electrolyte containing 5 g / L to 15 g / L of a nickel salt and 5 g / L to 20 g / L of a copper salt, and then heated at a liquid temperature of 25° C. to 45° C. and 1 A / dm 2 Up to 5A / dm 2 Electrolyze for 1 to 5 seconds at a current density of 1000 nm to perform a single plating step; and The primary plated copper foil is immersed in a secondary electrolyte containing 40 g / L to 70 g / L of a copper salt and 100 g / L to 150 g / L of sulfuric acid, and then heated at a liquid temperature of 25° C. to 45° C. and a current of 10 A / dm 2 Up to 20A / dm 2 The secondary plating is performed by electrolyzing for 1 to 5 seconds at a current density of .

10. A negative electrode for a secondary battery, comprising: The surface-treated copper foil according to any one of claims 1 to 8; as well as A negative electrode active material is coated on the surface-treated copper foil. 11 . The negative electrode according to claim 10 , wherein the negative electrode active material comprises carbon, metal, metal oxide, metal carbide or a combination thereof.

Citation Information

Patent Citations

  • Surface-treated copper foil and current collector, electrode and battery using same

    CN108400338A